MANIERA SEBAGAI MANIFESTASI KONSEP MA PADA KARYA INTERIOR ARATA ISOZAKI - Harmilyanti Sulistyani (Institut Seni Indonesia Surakarta, 2011)
Arata Isozaki is known as Japan's Postmodern architect. Japanese culture knowledge and the influence of Western clasissme are the advantages possessed of Isozaki. He combine the Japanese architecture that thick with the composition of form and detail with clasissme from the West. The view of eastern culture influences Isozaki productivity as interior architects to produce works that the artifacts spread in various parts of the world. The uniqueness of the works that influenced by family background and environment makes his work have more value.That’s way the Isozaki work so worthy to be explore to get a concept which is applied to his interior work.The purpose of this research is to find the embodiment of the Japanese concept called Ma on the Isozaki interior work. This article is the result of desk study research with rationalistic paradigm. Literature is used as a source of study. Statements and writings have ever published is the main source of study, the physical results of the interior work as the product is used to find the application from view in the work Isozaki.Maniera is the embodiment of traditional Japanese concept called Ma combined with mannerism from European used by Isozaki in his interior work. These conditions can’t be separated from the family that raised and pursued education environment. Although live in the modern era but he still maintaining Japan traditional values. From many different function, Isozaki's work shows the concept of Ma as a source of ideas on his interior work.Keywords: Arata Isozaki, interior, concept of Ma, Maniera.